Penundaan Kehamilan Dengan Memakai Alat Kontrasepsi Bagi Pengantin Baru Dalam Tinjauan Hukum Islam (Studi Di Kecamatan Selebar Kota Bengkulu) - Dasri, Dasri (UIN Fatmawati Sukarno Bengkulu, 2016)
Using of Contraception to Delay Pregnancy for Newlyweds in Islamic Law Review (Case Study in District of Selebar, Bengkulu City). This study raises the issue of the factors that cause the delay of pregnancy for newlyweds and legal substitute delay pregnancy for newlyweds in the district of Selebar, Bengkulu by using contraceptives according to maqasid sharia. The purpose of this study was to determine the factors that cause a delay of pregnancy for newlyweds and to determine the legal of delaying pregnancy for newlyweds in the district of Selebar, Bengkulu by using contraceptives according to maqasid Sharia. This study used qualitative methods, the data collection techniques used were observation, interviews and documentation, then after the data obtained were analyzed by deduction methodes, data presentation and conclusion. From the results of the study showed that the factors that cause delay pregnancy for a newlyweds in District of Selebar, Bengkulu city, are; economic factors, because the newlyweds cople still want to pursue a career, as well as a joint agreement between the husband and wife of not willing to have a children yet, while the use of contraceptives according to maqasid sharia to delay the pregnancy due to economic reasons and feared that the parents can not give education to the children, then it is permissible in Islam, but delaying the pregnancy by using contraception for reasons cople still want to pursue a career until his career reached the peak, then it is forbidden in Islam. However, Islam does not forbid totally the use of contraception but it has to be specific reasons, and acceptable.